New research programme of JAEA/CLADS to reduce the knowledge gaps revealed after an accident at Fukushima-1: introduction of boiling water reactor mock-up assembly degradation test programme. Issue 4 (2nd April 2020) - Pshenichnikov, Anton; Kurata, Masaki; Bottomley, David; Sato, Ikken; Nagae, Yuji; Yamazaki, Saishun
ABSTRACT: The new R&D programme of JAEA/CLADS tests complements the previous investigations related to BWR severe accidents. A series of tests aim at closing the gaps in understanding of the Fukushima Dai-Ichi degradation sequence at each unit. The paper emphasises the problem of control blade degradation, which influences the accident progression at an early stage and shows the approach for thorough investigation of this problem.